2019
DOI: 10.1155/2019/6530897
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Boarding and Alighting Ratio on Passengers’ Behaviour at Metro Stations by Laboratory Experiments

Abstract: The objective of this work was to study the effect of the ratio between passengers boarding and alighting on the passengers’ behaviour at metro stations. A mock-up of a vehicle and the relevant portion of the platform was built to run a series of simulation experiments at University College London’s Pedestrian Accessibility and Movement Environment Laboratory (PAMELA). Different scenarios were tested based on the next generation London Underground trains. The scenarios were classified according to different lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…It should be noted that the spatial characterization that a pedestrian has when combining a large part of these variables has already been studied previously. More recent studies done by Seriani et al [31] reported in different scenarios the effect of the ratio between passengers boarding and alighting, using a mock-up of a London Underground train at a laboratory facility. Using also experiments, Geoerg et al [32] studied the movement of passengers in a bottleneck and a corridor.…”
Section: Existing Studies On Space Occupied By Pedestriansmentioning
confidence: 99%
“…It should be noted that the spatial characterization that a pedestrian has when combining a large part of these variables has already been studied previously. More recent studies done by Seriani et al [31] reported in different scenarios the effect of the ratio between passengers boarding and alighting, using a mock-up of a London Underground train at a laboratory facility. Using also experiments, Geoerg et al [32] studied the movement of passengers in a bottleneck and a corridor.…”
Section: Existing Studies On Space Occupied By Pedestriansmentioning
confidence: 99%
“…Recently, some authors [34][35][36][37] reported that platform edge doors have no important impact on the dwell time, but the interaction is influenced by other variables such as the formation of lines of flow, distance between passengers, speed and space used by each passenger.…”
Section: Review Of Research On Dwell Timementioning
confidence: 99%
“…Therefore, several laboratory experiments are performed, including the Pedestrian Accessibility Movement Environment Laboratory (PAMELA). In a laboratory, certain variables can be changed while keeping the others constant, which allows the study of the influence of a single factor [35,37,65]. A series of experiments were conducted at the PAMELA using a full-size mock-up train carriage and a platform in order to obtain empirical evidence for the passenger boarding activities.…”
Section: Experiments Setupmentioning
confidence: 99%
“…As field studies are in most cases not suitable to analyse the effects of certain parameters independently, several experimental studies have been conducted in order to determine factors that have an influence on the boarding and alighting times. Exemplary variations performed were different ratios of boarding and alighting passengers [14] and train design factors (e.g., door widths and number of doors [11,[15][16][17][18][19], horizontal and vertical gap sizes [17,18,20,21], vestibule setback [17,18], boarding and alighting through different doors [22]). The types of passengers influence the boarding and alighting times, as age or the presence of luggage are factors that should be considered [23,24].…”
Section: Introductionmentioning
confidence: 99%